Pengaruh Mekanisme Corporate Governance dan Leverage terhadap Kinerja Keuangan Perusahaan - Hutomo, Vino Pancoro; , Drs. Sri Padmantyo, M.B.A (2015)
This study aims to know and to analyze the influence of corporate governance and leverage to financial performance in manufacturing companies who registered at the indonesian stock exchange 2011-2012, Whether partial and simultaneous. The indicators used to explain corporate governance in this research consisting of a board of directors , independent commissioner , and audit committee. The method of analysis that used in this research was linear regression multiple , according to research objectives which is to analyze variable influence independent dependent on variables. Sample used in the it is a whole manufacturing companies who registered at the indonesian stock exchange 2011- 2012. The determination of sample uses the method purposive sampling. By using the method is obtained 35 companies that will be used for sample in this research The results of the testing of hypotheses in this research , shows that board of directors do not affect in significant impact on financial performance. Independent commissioner do not affect in significant impact on financial performance. Audit committee do not affect in significant impact on financial performance. Leverage influential in a negative significant impact on financial performance.